Isolamento, caracterização e avaliação da atividade antimicrobiana de fungos endofíticos de Caesalpinia echinata Lam. (Leguminosae - caesalpinioideae) - Machado, Maria Aliete Bezerra Lima (2009)
The endophytic microorganisms in at least one phase of its life cycle inhabit the inner tissues of plants without causing apparent damage. Like other tropical species, Caesalpinia echinata Lam has shown several endophytes. Therefore this study aimed to isolate and characterize the endophytic fungi of Brazil wood, as well as assess the antimicrobial activity of extracts. The harvesting of stems has been done in a fragment of Atlantic Forest, and the leaves were harvested from trees growing in the campus of the Universidade Federal de Alagoas. There was a predominance of filamentous fungi compared to bacteria, in both, stems and leaves. By morphological and molecular analyses some endophytic fungi of C. echinata were identified, namely: Botryosphaeria rhodina, Xylaria multiplex and Pestalotiopsis sp. Among all the isolates ten fungi were selected for tests of antagonism against phytopathogenic fungi. The endophytic fungi Pestalotiopsis sp. Xylaria multiplex and Botryosphaeria rhodina were the most effective antagonists of Pythium debaryanum and Phytoththora palmivora. These results obtained in in vitro experiments support the possibility of the application of chemical extracts of the endophytic Botryosphaeria rhodina and Xylaria multiplex for the biological control of plant pathogens such as Rhizoctonia solani and Colletotrichum gloeosporioides. The mycelial growth of the pathogenic fungus Phomopsis sp. was not inhibited by endophytic Botryosphaeria rhodina, Pestalotiopsis sp and Xylaria multiplex. These same endophytes were also the most effective inhibiting the mycelial growth of phytopathogen Pestalotiopsis sp. Botryosphaeria rhodina, Xylaria multiplex, Pestalotiopsis sp. and C.e.A6.F4.c.b. have shown a higher amount of biomass when growing in BD medium incubated in the dark and without agitation. Extracts of the endophytic fungi of Caesalpinia echinata obtained from different solvents, have not shown antibacterial effect on Enterococcus faecalis, Pseudomonas aeruginosa and Staphylococcus aureus, in the concentrations used.